A Study on Economic Loss Caused by Cystic Ecinococcosis in Animals Slouhtered in Elazig ELET Corporation Sloughterhouse Between 1998 and 2000 Years - Kaplan, Mustafa; Kuk, Salih (Fırat University, 2002)
Aim: The present experiment was carried out to determine economic loss caused by cystic echinococcosis in the animals slaughtered in Elazıg ELET corporation slaughterhouse between 1998 and 2000 years. Material and Methods: The records of slaughterhouse were retrospectively investigated to determine the organs with cystic echinococcosis in the slaughtered animals, which include cows, sheep and goats. Results: The percentages of cystic echinococcosis was found to be 2.52%, 2.32% and 0.12%; 2.51%, 2.37% and 0.13%; 1.85%, 1.74% and 0% in the lung, liver and heart from the cows, sheep and goats, respectively. According to the company's wholesale prices, the economical loss due to cystic echinococcosis were 17.031.064.000 TL in the cows, 8.258.000. 000 TL in the sheep and the goats. Total economical loss was calculated as 29.099.064.000 TL. Conclusion: The incidence of location of cystic echinococcosis at liver, lung or heart in cows, sheep and goats is similar but reflection of this involvement to the economic loss is much higher in cows. These results indicate that cystic echinococcosis presents more important consequences in cows in terms of economic loss compared to sheep and goats.

Amaç: Bu çalışmada 1 Ocak 1998-31. 12. 2000 tarihlerini kapsayan 3 yıllık döneminde kesilen kasaplık hayvanlarda kistik ekinokokkozise (KE) bağlı oluşan ekonomik kayıpların boyutunun ve hayvan türlerine göre dağılımını araştırmayı amaçladık. Gereç ve Yöntem: Elazığ ELET AŞ. Kesimhane'sinde veteriner kayıt defterleri incelenerek bu dönemde kesimi yapılan hayvanlarda KE'lu organların hayvan türüne ve yıllara göre dağılımları irdelendi. Bulgular: Kesimi yapılan hayvanlarda akciğer, karaciğer ve kalpte KE yerleşme sıklığı sırasıyla sığırlarda %2.52, %2.32 ve %0.12 koyunlarda %2.51, %2.37 ve %0.13 keçilerde %1.85, %1.74 ve %0 olarak bulundu. Ekonomik değer olarak bakıldığında 3 yıllık süre içerisinde toplam ekonomik kaybın 29.099.064.000 TL olduğu bulunmuştur. Bunun 17.031.064.000 TL sığırlardaki, 8.258.000. 000 TL koyunlardaki ve 3.810.000.000 TL ise keçilerdeki ekonomik kayıp olduğu görüldü. Sonuç: Sığır, koyun ve keçilerde KE'nin karaciğer, akciğer ve kalbe benzer oranlarda yerleştiği ancak bu tutulum oranlarının ekonomik kayba yansımasının sığırlarda çok daha yüksek olduğu görülmektedir. Bu sonuçlar ekonomik değer açısından bakıldığında sığırlarda KE'nin koyun ve keçilere göre çok daha önemli olduğu görülmektedir.
1998-2000 YILLARI ARASINDA ELAZIĞ ELET AŞ KESİMHANESİNDE SAPTANAN KİSTİK EKİNOKOKKOZUN EKONOMİK KAYIP YÖNÜNDEN İRDELENMESİ